Effect of polysaccharide-based edible coatings incorporated with sodium benzoate on the control of postharvest black spot of organic cherry tomatoes caused by Alternaria alternata - Rodsamran, Patratip; Sothornvit, Rungsinee; Palou, Lluís; Pérez-Gago, María B. (ISHS, 2021)
Edible composite coatings based on hydroxypropyl methylcellulose (HPMC), commercial carboxymethylcellulose (CMC), CMC from rice stubble (CMCr) or sodium alginate (SA)-lipid were prepared with or without 2% (w/w) of the food preservative sodium benzoate (SB) and evaluated against postharvest black spot caused by the pathogen Alternaria alternata on artificially inoculated organic cherry tomatoes during either incubation at 20°C for up to 13 days or storage at 5°C for up to 19 days followed by a shelf life period of 3 days at 20°C. Disease incidence and severity (lesion diameter) were determined during storage and the 'area under the disease progress stairs' (AUDPS) was calculated. The addition of SB did not reduce disease incidence during incubation at 20°C. However, it significantly reduced black spot severity and AUDPS. Particularly, on fruit incubated at 20°C, the most effective antifungal coatings amended with SB for the control of black spot were those formulated with HPMC and CMCr (both with 10% total solid content (SC)), which reduced AUDPS values from 320 on uncoated tomatoes to 175 and 210, respectively. CMCr-SB coating was also the most effective on cherry tomatoes stored at 5°C, with AUDPS mean values for black spot at the end of the shelf life period of 120 as compared to 360 on uncoated controls. The fact that CMCr was extracted from rice stubble provides a potential use for this industrial by-product.